Biochemical composition of sedimentary organic matter in the coral reefs of Lakshadweep Archipelago, Indian Ocean. Issue 9 (21st October 2019) - Joy, Anu; Anoop, P.; Rajesh, R.; Mathew, Jose; Mathew, Angel; Gopinath, Anu
ABSTRACT: Surface sediments were collected from the shore and lagoons of Kavaratti, Kadamat Agatti and Pitti islands of Lakshadweep Archipelago during May 2015 and analysed for biochemical composition and quality of organic matter. The biochemical composition of sedimentary organic matter from the entire study area was characterised by the dominance of carbohydrates (CHO) followed by proteins (PRT) and finally lipids (LPD). PRT:CHO ratios were less than 1 and indicated the presence of aged organic matter in the islands. The poor nutritional quality of sediments to support benthic fauna was evident from the values of LPD:CHO ratios. The refractory nature of sediments and less availability of food to benthic source was supported by BPC:TOC ratios. Based on estimated ratios and biopolymeric carbon values, the trophic status of the study area was categorised as oligotrophic.